Trust, privacy, service quality, and brand image on the success of electronic customer relationship management - Muhammad Habil; Yunita Engriani (Operations Management and Information System Studies, 2023)
The purpose of this study was to analyze the effect of trust, privacy, service quality, and brand image on the success of E-CRM Lazada customers in the city of Padang with customer satisfaction as a mediating variable. The population in this study are Lazada application users in the city of Padang and have made transactions at Lazada in the last 6 months. The sampling technique used was purposive sampling. The number of samples in this study was 210 people. Data collection uses a questionnaire and is processed with SEM PLS4. The results of this study indicate that: (1) there is a significant influence between trust and E-CRM. (2) there is a significant influence between privacy and E-CRM. (3) there is a significant relationship between service quality and E-CRM. (4) there is a significant influence between Brand Image and E-CRM. (5) there is a significant relationship between trust and customer satisfaction. (6) there is a significant influence between privacy and customer satisfaction. (7) there is a significant influence between service quality and customer satisfaction. (8) there is a significant influence between brand image and customer satisfaction. (9) there is a significant influence between customer satisfaction and E-CRM. (10) There is a significant relationship between trust in E-CRM through customer satisfaction. (11) There is a significant influence between privacy on E-CRM through customer satisfaction. (12) There is a significant influence between service quality on E-CRM through customer satisfaction. (13) There is a significant influence between brand image on E-CRM through customer satisfaction.